1974
DOI: 10.1159/000459414
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Studies on Glycogen Storage Diseases

Abstract: Studies have been conducted on three types of glycogen storage diseases: (1) the molecular heterogeneity of muscle phosphorylase deficiency (type V) has been shown by demonstration of the presence of cross-reacting immunological material in one out of two cases; (2) the presence of cross-reacting material has been demonstrated in 18 tissue samples from patients with amylo-1,6-glucosidase deficiency (type III); (3) the existence of pathological variants of amylo-1,4-glucosidase (type II) has been shown by elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

1978
1978
1994
1994

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 15 publications
2
2
0
Order By: Relevance
“…These values are compatible with each being heterozygous for McArdle's syndrome, albeit there may be a tendency for the amounts to be somewhat less than 50%. The normal values of phosphorylase observed in this study are consistent with previously reported values (10,(25)(26)(27) (29) and Chance (30). Resting pH of flexor digitorum superficialis, as observed by this technique in normal healthy volunteers, was 7.03±0.01 (±SEM, n = 22).…”
Section: Resultssupporting
confidence: 93%
“…These values are compatible with each being heterozygous for McArdle's syndrome, albeit there may be a tendency for the amounts to be somewhat less than 50%. The normal values of phosphorylase observed in this study are consistent with previously reported values (10,(25)(26)(27) (29) and Chance (30). Resting pH of flexor digitorum superficialis, as observed by this technique in normal healthy volunteers, was 7.03±0.01 (±SEM, n = 22).…”
Section: Resultssupporting
confidence: 93%
“…The same column, fully loaded with acid a-glucosidase and thoroughly washed with standard buffer, did not release any a-glucosidase activity when eluted with extracts from affected muscle, although activity was readily released by 0.04 M-citrate buffer, pH 3.0, once again indicating a lack of cross-reacting material. This finding is consistent with those of de Barsy et al (1972), Dreyfus et al (1974) and Murray et al (1978), who were not able to detect cross-reacting material in tissues of human patients suffering from glycogenosis type II. However, this is in conflict with the work of Beratis et al (1978), who reported the presence of cross-reacting material in cultured fibroblasts of human patients suffering from the infantile and the adult forms of glycogenosis type II.…”
Section: Fig 1 Chromatography Of Bovine Skeletal-muscle Aglucosidassupporting
confidence: 93%
“…In addition, the mutant enzyme showed an increased mobility by cellulose acetate electrophoresis (26). The findings of the mixing experiment suggest that the enzyme deficiency in the adult acid a-glucosidase de tivity was present in the enzyme-antibody precipitate from normal crude placental and normal skin fibroblast extracts, and from purified enzyme from normal tissues.…”
Section: Resultsmentioning
confidence: 86%
“…The specific activity and the Vmax of the purified acid a-glucosidase from the adult acid a-glucosidase deficiency fibroblasts were 10 and 6.5% of the purified normal enzyme, respectively, but the Michaelis con- heat inactivation rate was observed between the enzyme from normal and from the adult form of the deficiency, an increased resistance to heat has been reported in crude lysates from two such patients (26). In addition, the mutant enzyme showed an increased mobility by cellulose acetate electrophoresis (26).…”
Section: Resultsmentioning
confidence: 91%